Resposta :
b)
[tex]x - 12 = \frac{3x}{4} \\ x - \frac{3x}{4} = 12 \\ \\ \frac{4x - 3x}{4} = 12 \\ \\ \frac{x}{4} = 12 \\ \\ x = 12 \times 4 = 48 [/tex]
c)
[tex] \\ 3x - 40 = \frac{x}{2} + 20 \\ 3x - \frac{x}{2} = 20 + 40 \\ \frac{6x - x}{2} = 60 \\ \frac{5x}{2} = 60 \\ x = 60 \times \frac{2}{5} = \frac{120}{5} = 24[/tex]
d)
[tex] \\ \frac{x}{2} + 10 + \frac{x}{3} = x \\ \frac{x}{2} + \frac{x}{3} - x = - 10 \\ \frac{3x + 2x - 6x}{6} = - 10 \\ - \frac{x}{6} = - 10 \\ - x = - 10 \times6 \\ x = 60[/tex]
Multiplicando -x = -60 por menos, a expressão torna positiva